Pathomorphological changes of capillaries in the cerebral cortex in type 2 diabetes mellitus - V. O. Tumanskyi; Yu. M. Avramenko (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki, 2021)
The aim of the study was to determine microscopic, immunohistochemical, electron microscopic, morphometric parameters of capillaries in the cerebral cortex in deceased patients with type 2 diabetes mellitus (DM) in comparison with the conditional control group and the group of deceased patients with dyscirculatory ischemic encephalopathy.